PENERAPAN SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KECURANGAN AKUNTANSI PADA BANK PERKREDITAN RAKYAT KOTA BATAM: PENERAPAN SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP KECURANGAN AKUNTANSI PADA BANK PERKREDITAN RAKYAT KOTA BATAM - Dian Efriyenty (JURNAL AKUNTANSI BARELANG, 2020)
The phenomenon associated with the occurrence of fraud in BPR is that it is closely related to the role of BPR internal control, which does not systematically oversee leadership in monitoring, evaluating and reporting all processes and stages of activities. As in the case of an error at BPR Nusamba, one of the employees who collects savings and credit installments, must be deposited with client money but extortion occurs on BPR Nusamba cash, with the amount of money reaching Rp 115,429,909. The sample of this study was respondents who received authority in the use of funds in 27 BPR Batam City units. The results of the study stated that partially and simultaneously the application of accounting information systems and internal controls significantly influence accounting fraud.